Functional analysis of Spodoptera frugiperda nucleopolyhedrovirus late expression factors in Sf9 cells - Berretta, Marcelo Facundo (2013)
We used transient expression assays to assess the function of the baculovirus Spodoptera frugiperda M nucleopolyhedrovirus (SfMNPV) homologs of Autographa californica MNPV (AcMNPV) factors involved in late gene expression (lefs), in the Sf9 insect cell-line, which is permissive for both viruses. It is well-established that nineteen AcMNPV lefs support optimal levels of activity from a late promoter-reporter gene cassette in this assay. A subgroup of SfMNPV lefs predicted to function in transcription-specific events substituted the corresponding AcMNPV lefs very efficiently. When all SfMNPV lefs were assayed, including replication lefs, activity was low, but addition of two AcMNPV lefs not encoded in SfMNPV genome, resulted in augmented reporter activity. SfMNPV IE-1 was able to activate an early promoter cis-linked to an hr-derived element from SfMNPV but not from AcMNPV. However, the level of early promoter activation with SfMNPV IE-1 was lower compared to AcMNPV IE-1.